Timing, kinematics, and tectonic significance of strike-slip fault systems in the Atacama Desert of northern Chile and the Lower Colorado River corridor, U.S.A. - Mavor, Skyler, author; Singleton, John, advisor; Gallen, Sean, committee member; Ridley, John, committee member; Laituri, Melinda, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Zip file contains data spreadsheets and plates 1, 2 and 3.
Keywords: strike-slip system; plate-boundary oblique motion; intra-arc faults; fault systems